Thermithiobacillus plumbiphilus AAFK—Arsenic-Resistant Bacteria Isolated from Arsenopyrite Material - Artem Shaikin; Anton Zvonarev; Mikhail Vainshtein; Tatiana Abashina (Microbiology Research)
Autotrophic sulfur-oxidizing bacteria can play a key role in the metal bioleaching from low-grade sulfide-containing ores. The most commonly used bioleaching group is presented with acidophilic bacteria of the order Acidithiobacillales. We studied the diversity of bacteria in the arsenopyrite gold-bearing ore and also discovered a wide distribution of neutrophilic non-thermophilic bacteria Thermithiobacillus plumbiphilus in this ore, as well as its drainage and flotation concentrate. For the first time, T. plumbiphilus was isolated from the natural arsenic-containing mineral material. The first description of complete genome for the species T. plumbiphilus was also carried out and discovered genes providing the As resistance. Culturing the isolated strain T. plumbiphilus AAFK confirmed the found bacterial resistance to arsenite and cocadylate during the effective thiosulfate oxidation. Experiments on the arsenopyrite bioleaching showed that T. plumbiphilus AAFK can be used as an auxiliary bacterial culture capable of oxidizing reduced / intermediate sulfur compounds. The genetic basis of the T. plumbiphilus AAFK resistance to the arsenic compounds is discussed; the mechanisms are similar with the ones known for acidophilic thiobacilli. The biofilm formation is shown for the first time for T. plumbiphilus; presumably, it could provide some protection and immobilization of the cells. Structures of the T. plumbiphilus AAFK cells and their production of outer membrane vesicles are described and discussed.